Effective Communication Model in the Practice of Implementing Occupational Health and Safety Management System through Social Constructivism Approach - Ridwanudin, Oce (Business Education Program of Universitas Pendidikan Indonesia, 2024)
This research aims to design an effective communication model related to the implementation of the Occupational Health and Safety Management System (OHSMS) through a social constructivism approach at PT Unilever Indonesia, Tbk., Cikarang Factory. A descriptive survey was used in this research by distributing closed questionnaires, with purposive sampling. The results of data collection were processed using SPSS 27 software. The research results indicated that the company's OHSMS socialization through the Safety Manager was still not optimal. For this reason, in order to improve the quality of communication and employee understanding regarding the implementation of OHSMS in companies, researchers designed an effective communication model using a social constructivism approach, which includes five stages, namely: 1) communication evaluation stage; 2) exploration stage; 3) concept and skills development stage; 4) stage of applying concepts and skills; and 5) reflection stage.